Surface Passivation and Antireflection Behavior of ALD TiO2 on n-Type Silicon for Solar Cells. (28th November 2013) - Yu, Ing-Song; Wang, Yu-Wun; Cheng, Hsyi-En; Yang, Zu-Po; Lin, Chun-Tin
Abstract : Atomic layer deposition, a method of excellent step coverage and conformal deposition, was used to deposit TiO2 thin films for the surface passivation and antireflection coating of silicon solar cells. TiO2 thin films deposited at different temperatures (200°C, 300°C, 400°C, and 500°C) on FZ n-type silicon wafers are in the thickness of 66.4 nm ± 1.1 nm and in the form of self-limiting growth. For the properties of surface passivation, Si surface is effectively passivated by the 200°C deposition TiO2 thin film. Its effective minority carrier lifetime, measured by the photoconductance decay method, is improved 133% at the injection level of 1 × 10 15  cm −3 . Depending on different deposition parameters and annealing processes, we can control the crystallinity of TiO2 and find low-temperature TiO2 phase (anatase) better passivation performance than the high-temperature one (rutile), which is consistent with the results of work function measured by Kelvin probe. In addition, TiO2 thin films on polished Si wafer serve as good ARC layers with refractive index between 2.13 and 2.44 at 632.8 nm. Weighted average reflectance at AM1.5G reduces more than half after the deposition of TiO2 . Finally, surface passivation and antireflection properties of TiO2 are stable after the cofire process of conventional crystalline Si solar cells.